A comparison of biological activity of commercially available purified native botulinum neurotoxin serotypes A1 to F1 in vitro, ex vivo, and in vivo. Issue 6 (22nd November 2018) - Donald, Sarah; Elliott, Mark; Gray, Bryony; Hornby, Fraser; Lewandowska, Agnieszka; Marlin, Sandra; Favre‐Guilmard, Christine; Périer, Cindy; Cornet, Sylvie; Kalinichev, Mikhail; Krupp, Johannes; Fonfria, Elena
Abstract: Botulinum neurotoxin (BoNT) is a major therapeutic agent. Of seven native BoNT serotypes (A to G), only A and B are currently used in the clinic. Here we compared the potency of commercially available purified native serotypes A1 to F1 across in vitro, ex vivo, and in vivo assays. BoNT potency in vitro was assessed in rat primary cells (target protein cleavage and neurotransmitter release assays) in supraspinal, spinal, and sensory systems. BoNT potency ex vivo was measured in the mouse phrenic nerve hemidiaphragm (PNHD) assay, measuring muscle contractility. In vivo, BoNT‐induced muscle relaxation in mice and rats was assessed in the Digit Abduction Score (DAS) test, while effects on body weight (BW) gain were used to assess tolerability. In all assays, all BoNT serotypes were potent toxins, except serotype D1 in vivo which failed to produce significant muscle flaccidity in mice and rats. In rats, all serotypes were well‐tolerated, whereas in mice, reductions in BW were detected at high doses. Serotype A1 was the most potent serotype across in vitro, ex vivo, and in vivo assays. The rank order of potency of the serotypes revealed differences among assays. For example, species‐specificity was seen for serotype B1, and to a lesser extent for serotype C1. Serotypes F1 and C1, not currently in the clinic, showed preference for sensory over motor models and therefore could be considered for development in conditions involving the somatosensory system.